Holistic Parenting Method from al-Qur'an Perspective: Strengthening Family Resilience in Facing the Dynamics of Modern Life - Muammar Khadafi; Muhammad Ulul Azmi (Saniya Institute, 2024)
Modern life is increasingly complex and dynamic, family resilience is a very crucial issue and the challenges are becoming more and more real. Family resilience refers to the ability of a family to survive, adapt, and thrive despite various pressures and challenges. The goal of this research is to create families that have the ability to adapt to these changes while still maintaining their values and integrity. The internalization of Islamic values in the family. For the type of research